Dance students at a two year college: making sense of their academic, cultural, and social world. Issue 2 (4th May 2019) - Lopez, Benjamin
ABSTRACT: This qualitative study investigated the lived experiences of six community college dance students. The theoretical framework of social cognitive career theory was used but was modified to include only the tenets most frequently cited in the literature that directly influenced the career identity of dancers particularly in relation to their motivation to academically persist and graduate. The research provides insight into the individual experiences of the participants in their dance journey. The goal was to obtain current data on the student experience so that dance programs can further enhance the student experience. The phenomenological analysis produced an early thematic matrix of 18 codes that were reduced to six major themes. Of those six themes, this study will focus on academic commitment, dance identification, and challenges.